(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of different demographic and haematological features of patients diagnosed to have aplastic anemia, Study Design: Purposive, case-series study. Place and Duration of Study: This study was conducted at the Department of Pathology, King Edward Medical University Lahore from January 2007 to December 2014. Materials and Methods: One hundred and forty-six consecutive aplastic anemia cases were included. The sociodemographic details, medical history, environmental, clinical and haematological features were included. Results: The median age of patients was 28 years, 75 were female and 71 male. The disease was graded according to severity and results were as follows: 1) non-severe 50%, 2) severe 34% and 3) very severe aplastic anemia 16%. Majority of patients were from low socioeconomic 57.5% or middle class 32%. Conclusion: Aplastic anemia shows almost equal sex distribution. Non-severe aplastic anemia is the most common type of aplastic anemia presenting in a diagnostic set up of a tertiary care hospital.